Transformasi Pembelajaran Matematika melalui Alat Peraga Inovatif: Pendekatan Partisipatif untuk Meningkatkan Pemahaman Konsep dan Kreativitas Siswa - Wilminche M. D E. L. Kelen (FKIP, Universitas Palangka Raya, 2026)
Various studies indicate that mathematics learning in schools is still dominated by teacher-centered methods that emphasize abstract concepts, resulting in limited connection to real-life contexts and low student engagement. Therefore, innovative learning approaches are needed to bridge mathematical concepts with real-world experiences while encouraging active student participation. This community service activity aims to enhance students’ conceptual understanding and creativity through the use of innovative mathematics teaching aids within a participatory approach. The method employed is descriptive-implementative, consisting of needs analysis, training implementation, and evaluation stages. Data were collected through concept understanding tests, mathematical creativity tests, observations, and interviews, and were analyzed using both quantitative and qualitative approaches. The results show an improvement in students’ conceptual understanding as well as the development of mathematical creativity, indicated by increased fluency, flexibility, and originality in problem-solving. In addition, students’ active participation in the learning process significantly improved. The use of teaching aids proved effective in creating more meaningful learning experiences through direct interaction with mathematical concepts. In conclusion, the use of mathematics teaching aids in participatory-based learning is effective in improving the quality of learning, particularly in terms of students’ conceptual understanding and creativity.